Menurunnya Semangat Mengajar: Krisis Motivasi Guru dalam Tekanan Tugas dan Tuntutan Sistem Pendidikan Modern - Robi’ah Robi’ah; Lukluk Sofiatil Jannah; Dian Febri Ovianti; Rina Diniati; Sri Hartati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the decline in teaching enthusiasm among educators as a result of a motivation crisis driven by the pressures of workload and the demands of the modern education system. The purpose of this research is to evaluate the impact of this motivational decline on the quality of the learning process and to identify both internal and external factors that exacerbate the issue. The findings reveal that reduced teaching enthusiasm significantly affects teacher-student interaction, instructional innovation, and student learning outcomes. However, the study also found that institutional support, continuous professional development, and opportunities for professional reflection can help restore teacher motivation. This research recommends the development of more humane and responsive education that address the real needs of teachers in order to sustain the quality of education.